Gymnastics in higher education: reflections on assessment - Michele Viviene CARBINATTO; Myrian NUNOMURA (Escola de Educação Física e Esporte da Universidade de São Paulo (EEFEUSP), 2016)
Abstract Assessment procedures were based on the traditional educational paradigms of linearity and sequence, whose aim was to categorize and select individuals. With the advancement of Social and Human Sciences, assessments gained both a reflexive and an analytical characteristic and now they constitute a system of support and guidance for individual and group learning, all without losing sight of building character in the students. Supported by qualitative research, this study identified and discussed the assessments used by 14 university lecturers in the state of São Paulo who teach Gymnastics in the Physical Education undergraduate courses. The results showed different formats of assessment, namely: theoretical; debates; practical/experience; research; self-assessment and peer-review. None of the evaluated lecturers clearly stated the assessment criteria, becoming it, mainly, subjective. Four lecturers gave indication of using the assessment tools in the formative conception and only one lecturer guides its practice during the teaching-learning process after analyzing what has been detected in assessments.